Energy Transmission Protocols for Wireless Sensor Networks: A Review (International Journal of Engineering and Computer Science, 2014)
Data Routing though being the most basic service provided by the Wireless Sensor Network (WSN) Nodes, it is also the one which consumes the highest amount of energy. Sensor Nodes are usually fitted with power sources that are non-rechargeable and due to the vast application of WSNs they are also usually practically irreplaceable. This makes the longevity of Nodes a critical factor for consideration while designing the routing protocols. In this paper we survey the protocols that are being used and show their efficiency.